The Relationship Between Adequacy of Hemodialysis and Anemia in Chronic Kidney Diseases (Ckd) Patients Undergoing Hemodialysis in Dialysis Unit, Fatmawati Hospital - Leo Ginting; Abdul Aziz; Wulandari Wulandari; Dwi Budi Lasono (The Avicenna Medical Journal, 2021)
Background: Anemia is a common problem that often occurs in patients with CKD undergoing hemodialysis. 56.5% of hemodialysis patients were still have anemia, while on the other hand, the achievement of hemodialysis.  adequacy only reached 52.7%. Disparity that data is the basis for this research. The aim of this study is to analysis the relationship between the achievement of hemodialysis adequacy with the incidence of anemia in patients with CKD undergoing hemodialysis.Methods: This study uses a descriptive correlation with a cross sectional approach to the analysis of the independent variable (HD Adequacy) and the dependent variable (Anemia). The relationship between these variables was tested using the Chi Square test.Result: The study was conducted on 134 hemodialysis patients aged 13-86 years, the most common vascular access was AV fistula (68.7%), and women were the most respondents (55.2%). The Kt / V value in this study was 1.67 (1.03-2.75) and an adequate one was 54.5%. Adequate URR reached 80.6% with a mean of 75.13 ± 6.38. The incidence of anemia reached 53.7% with the Hb value at 8.93 ± 2.82 mg / dl. The results of the Chi Square test showed that HD adequacy (Kt / V and URR) with the incidence of anemia had P values of 0.670 and 0.217.Conclusion: There is no significant relationship between HD adequacy and the incidence of anemia